Enantioselective extraction of unprotected amino acids coupled with racemization - Haofei Huang (Nature Portfolio, 2021)
Dynamic kinetic resolution is a common approach for the preparation of optically pure amino acids using enzymes. Here the authors report an alternative method based on enantioselective extraction coupled with racemization, in which a bulky extractant affords hydrophobic extractable imines with amino acids rapidly, reversibly and enantioselectively.